Wars from within understanding and managing insurgent movements - Schnabel, Albrecht; Gunaratna, Rohan (Imperial College Press insurgency and terrorism series, 2015)
Wars from Within brings together an international and multidisciplinary group of academics and practitioner-researchers specializing in the study of insurgent movements in order to provide a deeper understanding of the violent manifestations of insurgencies in different parts of the world.